Analisis Sintaksis dalam Teks Berita Pernyataan Ketua DPR RI Mengenai Kasus Dokter PPDS Universitas Padjajaran - Andini Ridwana; Elisabet Simanjuntak; Raisha Mei Nabel Pakpahan; Sinta Sianipar; Anggia Puteri; Frinawaty Lestarina Barus (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This study aims to analyze the syntactic structure and function in a news text containing the statement of the Speaker of the Indonesian House of Representatives (DPR RI) regarding the case of a specialist medical education (PPDS) student at Padjadjaran University (UNPAD). The focus of this research is on identifying clauses, phrases, and sentence patterns, including syntactic errors found in the online news article. A descriptive qualitative method was used with a syntactic analysis approach. The results show that the news text contains a variety of simple and complex clause structures with syntactic functions that serve to deliver informative and persuasive messages. However, several syntactic errors were also found, such as ineffective sentence construction, phrase misplacement, and ambiguous meanings. These findings highlight the importance of syntactic accuracy in news writing to ensure clarity and precision of information. This research is expected to contribute to the field of syntax studies and help improve language quality in mass media writing.